Strategia finansowania działalności samorządu gminnego - Zawora, Jolanta (Strategies for Financing Activities of Local Government Authorities, 2009)
All activities being undertaken by Local Government Authorities ought to be anchored in long-term approaches. Taking into account the risk of liquidity problems associated with benefiting from varied sources and methods of financing local government projects, it is possible to identify three key concepts of financing such activities such as passive, moderate, and active strategies. Appropriate feasibility studies together with practical application of financing strategies do enhance a high level realization of local government projects especially if the project scale and sources of financing are mutually tailored
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 379-386